Thrace's Gateway to Anatolia and the Aegean in the Bronze Age: Maydos-Kilisetepe - Sazci, Göksel; Mutlu, Meral Başaran (Archaeopress, 2023)
In excavations since 2010 at the Maydos-Kilisetepe mound on the European side of the Dardanelles, eight layers have so far been identified dating mainly from the Bronze Age. Base rock has not yet been reached. While associations with Thrace in north-west Anatolia have been traced back to the Early Iron Age, analysis of ceramic finds at Maydos-Kilisetepe have revealed connections with the Balkans from the earliest layer currently reached. Other retrieved finds suggest that the settlement was related to both the Black Sea and Aegean regions throughout the Bronze Age. Considering archaeological deposits in the Aegean, the Bronze Age in the Troad was first evaluated by H. Schliemann and C. W. Blegen following excavations at Troy. This was then discussed in association with Anatolian archaeology as a result of recent excavations at Beşik-Yassitepe and Troy by M. Korfmann. It was affirmed by results of excavations at Maydos-Kilisetepe that the region should also be evaluated in consideration of Balkan archaeological deposits. © the individual authors and Archaeopress 2023. All rights reserved.
Keywords: Balkan; Bronze age; Ceramic; Maydos Kilisetepe Mound; Northwest Anatolia